Determinants of Spatial Land Use Strategy for Transformation of Land towards Sustainable Development in Kenya - Bonface E. Ekabten; Leonard S. Mulongo; Peter O. Isaboke (New Visions in Science and Technology Vol. 5, 2021)
Across the world, numerous land use strategies have been deployed to manage activities on, under and or above land. However, the pressure exerted on land as a result of anthropogenic and effects of climate change have been acknowledged in creating imbalances between different land uses. Spatial land use strategy seeks to promote internal linkages within key sectors of the economy while at the same time mitigating on the factors that may impede on external orientations. This paper examined the effect of Spatial Land Use Management Strategy as a tool for transformation towards sustainable development with a focus to Vihiga County in Western Kenya. The study objectives included; assessing the current Spatial Land Use activities on sustainable livelihood, examining the determinants of Spatial Land Use Strategy in Vihiga County, evaluating the influence of Spatial Land Use Strategy on sustainable livelihood, and to analyze the effects of the challenges attributed to various land use activities on sustainable livelihood. The findings as based on the methodology indicate that the geo-physical, social, economic and political dimensions were identified as major determinants of the applicability of the strategy, although agriculture and commerce were more prevalent land uses. Further, it’s possible to integrate the variables and datasets in order to develop effective and holistic spatial land use scenarios as a basis for a paradigm shift in planning and attaining sustainable development.